Faktor Ketidakpatuhan Minum Obat pada Pasien Skizofrenia - Silvia Agustina Ahmadi; Prastiwi Puji Rahayu; Deasti Nurmaguphita (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Long-term treatment adherence is critical for schizophrenia patients, yet non-adherence remains a significant global challenge, contributing to relapse, re-hospitalization, and increased healthcare costs. Understanding the underlying multidimensional factors is crucial for developing effective interventions. This systematic literature review aims to identify and categorize the dominant factors contributing to medication non-adherence among schizophrenia patients, based on current quantitative evidence (2019-2024). A systematic search of Google Scholar and PubMed targeted quantitative cross-sectional studies using the PICOST framework. Article selection followed PRISMA guidelines, and quality was assessed using the JBI Critical Appraisal Checklist. Seven articles were included in the final narrative synthesis. The synthesis confirms that non-adherence is multifactorial. Identified factors were categorized into three groups: (1) Patient-related factors (e.g., poor illness insight, feeling cured, treatment fatigue); (2) Treatment-related factors (e.g., medication side effects, therapy duration); and (3) System and social factors (e.g., low family support, stigma, poor therapeutic alliance). Non-adherence is a complex issue arising from the interplay of patient, treatment, and social factors. Low family support and poor patient knowledge consistently emerge as key determinants. Interventions require a holistic approach extending beyond pharmacotherapy, focusing on comprehensive psychosocial education for patients and families, active side-effect management, and strengthening the family's role in care.